Pengelolaan supervisi akademik di SDN Tegalrejo Kecamatan Laweyan Kota Surakarta - YULIANA THERESIA, SUMARMI (2016)
The purpose of the research to gain illustration about academic supervision implementation in the main is: Characteristic of academic supervision preparation, Characteristic of academic supervision implementation and Characteristic of the advantage academic supervision implementation. The method of this research is qualitative research. The research location was at Tegalrejo Primary School in Laweyan, Surakarta. Technique of data collection used observation, interview and documentation. The data analysis is descriptive qualitative with the steps of data collection, data reduction, data service, and conclusion. Examination of validity data used triangulation technique. Based on the research, the result has gained: (1) Academic supervision preparation at Tegalrejo Primary School in Laweyan, Surakarta was done such as document preparation before, teacher preparation and instrument preparation. (2) Academic supervision implementation at Tegalrejo Primary School was done democratically, academic supervision is done when the teacher was performing the learning process in class after have done clarification. (3) The performance of academic supervision at Tegalrejo Primary School in Laweyan, Surakarta took some advantages namely there was an increase of teacher and student competence. Teacher become discipline to arrange learning instrument and performed learning process in class with method and also innovative approach, mean with student got achievement nor nonacademic.